Second malignant neoplasms after treatment of 1487 children and adolescents with acute lymphoblastic leukemia—A population‐based analysis of the Austrian ALL‐BFM Study Group. Issue 3 (12th June 2022) - Poyer, Fiona; Dieckmann, Karin; Dworzak, Michael; Tamesberger, Melanie; Haas, Oskar; Jones, Neil; Nebral, Karin; Köhrer, Stefan; Moser, Reinhard; Kropshofer, Gabriele; Peters, Christina; Urban, Christian; et al.
Abstract: Second malignant neoplasms (SMN) after primary childhood acute lymphoblastic leukemia (ALL) are rare. Among 1487 ALL patients diagnosed between 1981 and 2010 in Austria, the 10‐year cumulative incidence of an SMN was 1.1% ± 0.3%. There was no difference in the 10‐year incidence of SMNs with regard to diagnostic‐, response‐ and therapy‐related ALL characteristics except for a significantly higher incidence in patients with leukocytes ≥50.0 G/L at ALL diagnosis (2.1% ± 1.0% vs. 0% for 20.0–50.0 G/L, and 1.0% ± 0.3% for < 20.0 G/L; p  = 0.033). Notably, there was no significant difference in the incidence of SMNs between patients with or without cranial radiotherapy (1.2% ± 0.5% vs. 0.8% ± 0.3%; p  = 0.295). Future strategies must decrease the incidence of SMNs, as this event still leads to death in one‐third (7/19) of the patients.